The Effect of a Web-Based Energy Conservation Intervention on Fatigue Scores Among Patients With Heart Failure - Tasya Putri Aulia; Siti Wasliyah (Critical Medical and Surgical Nursing Journal, 2026)
Introduction: Heart failure is commonly associated with fatigue, which negatively affects physical functioning and quality of life. Website-based energy conservation education may improve access to educational resources and support fatigue management. This study evaluated the effect of website-based energy conservation education on fatigue among patients with heart failure. Method: A quasi-experimental study with a pre-test–post-test control group design was conducted in a secondary healthcare setting. Thirty-six patients with heart failure were recruited using consecutive sampling and allocated to an intervention group (n = 18) or a control group (n = 18). The intervention group received website-based energy conservation education, whereas the control group received leaflet-based education. Fatigue was assessed using the Fatigue Assessment Scale (FAS). Data were analyzed using paired and independent t-tests with a significance level of p < 0.05. Results: The mean fatigue score in the intervention group significantly decreased from 29.44 to 22.78 after the intervention (mean difference = 6.67; 95% CI: 6.25–7.08; paired t-test, p < 0.001). The control group also demonstrated a statistically significant reduction (mean difference = 0.39; 95% CI: 0.09–0.69; paired t-test, p = 0.015), although the improvement was substantially smaller. Independent t-test analysis showed a significant difference in post-intervention fatigue scores between the two groups (p < 0.001). Conclusions: Website-based energy conservation education was more effective than leaflet-based education in reducing fatigue among patients with heart failure. This intervention may serve as a practical nursing strategy to support fatigue management in this population.